2002
DOI: 10.1063/1.1479757
|View full text |Cite
|
Sign up to set email alerts
|

Strain relaxation of SiGe islands on compliant oxide

Abstract: The relaxation of patterned, compressively strained, epitaxial Si0.7Ge0.3 films transferred to borophosphorosilicate (BPSG) glass by a wafer-bonding and etch-back technique was studied as an approach for fabricating defect-free Si1−xGex relaxed films. Both the desired in-plane expansion and undesired buckling of the films concurrently contribute to the relaxation. Their relative role in the relaxation process was examined experimentally and by modeling. Using x-ray diffraction, Raman scattering and atomic forc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 18 publications
(14 reference statements)
1
58
0
Order By: Relevance
“…The stress/strain at the bimaterial interface induced by the lattice mismatch can also cause wrinkling, or variably called corrugation, undulation, convolution and ripples of a thin film [7][8][9][10][11] . Liu et al [11] reported that germanium (Ge) deposition dots on the compliant thin silicon film of Silicon-on-Insulator (SOI) substrates cause the local bending mode of a compliant film as shown in Fig.1.…”
Section: Introductionmentioning
confidence: 99%
“…The stress/strain at the bimaterial interface induced by the lattice mismatch can also cause wrinkling, or variably called corrugation, undulation, convolution and ripples of a thin film [7][8][9][10][11] . Liu et al [11] reported that germanium (Ge) deposition dots on the compliant thin silicon film of Silicon-on-Insulator (SOI) substrates cause the local bending mode of a compliant film as shown in Fig.1.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 7 plots the experimental data for 30 nm and 60 nm thick SiGe films [33] . The predictions of the linear perturbation analysis correspond to the straight lines in Fig.7.…”
Section: The Fastest Amplifying Wrinkles Obey A(t) = Aoexp(smt)mentioning
confidence: 99%
“…The shear lag model has also been formulated in two dimensions [39], and solved numerically for the expansion of a square island [27]. Figure 5 plots the strain scaled by the initial mismatch strain, against the time scaled by the square of the island size [33] . With such scaling, the shear lag model predicts one single curve in each plot for all island sizes.…”
Section: Oxlmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many different stress relief mechanisms observed in thin films. The residual stress can be partially relieved by plastic deformation and surface reconstruction [6], or simply by mechanical film failure, especially if the stress levels are high, and, in addition, externally applied mechanical and thermal stresses are present combined with environmental effects. In some cases, films and protective coatings fail due to environmental effects and long-term moisture exposure, causing corrosion of the substrate, or the film, or both.…”
Section: Introductionmentioning
confidence: 99%